PENGARUH BUDAYA SEKOLAH DAN SUPERVISI AKADEMIK TERHADAP KOMITMEN GURU MADRASAH IBTIDAIYAH SWASTA KECAMATAN PONTIANAK BARAT - Indawati, Sri Wahyu (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research generally aims to reveal the influence of school culture and academic supervision of teachers' commitment to SDI/Private MI West Pontianak using a quantitative approach with survey method and correlation analysis techniques. Data were collected using a questionnaire with Likert scale measurement model. The population in this research were 129 teachers. While the sample amounted to 98 teachers. The collected data is tabulated. Then analyzed with the help of a computer application program, ie SPSS version 17.0. Statistical data analysis using descriptive and inferential statistics. The initial step in testing the hypothesis with the test requirements regression analysis (normality test, homogeneity and linearity test). After the test analysis requirements are met, then the hypothesis testing. The analysis technique used is multiple regression analysis. To determine the effect of independent variables on the dependent variable is jointly used by test F. The conclusion of this study as follows 1) a school culture SDIS / MIS West Pontianak is high and the effect on the commitment of teachers, it means that the higher the school culture will increase teacher commitment, 2) academic supervision SDIS / MIS West Pontianak is quite good and the effect on the commitment of teachers, means the commitment of teachers will be increased if the better the academic supervision, 3) commitment of teachers SDIS / MIS West Pontianak is high because it is influenced by the culture of the school and academic supervision, meaning the higher the school culture and academic supervision will be higher the commitment of teachers. Keywords : School Culture, Academic Supervision, Teacher Commitment